Protection of Natural Environment and Cultural Property during Armed Conflict: An International Humanitarian Law Perspective - Pandey, Ashutosh (Unity Journal, 2024)
With the evolution and development of jus in bello, conflicts of both internal and international character have given due consideration to limit human casualties and minimize suffering. Post-World War trials in Nuremberg and Tokyo played a crucial role in influencing modern International Criminal Law. The international community soon realized the necessity to draft various international legal documents and establish the International Criminal Court to prosecute individuals for various categories of crimes including War Crimes. Article 8 of the Rome Statute has classified acts of destruction of the natural environment and cultural property within the ambit of the definition of War Crime. However, with a higher threshold required to prove the crime of destruction of the natural environment and a human rights approach taken in cases of destruction of cultural property, both areas seem to need much exploration and research. This paper scrutinizes the development of laws of war and dives deep into the jurisprudence laid down in various decisions of the ICC to protect these civilian objects during armed conflict. It further elucidates the lacunas in the law and explains how they may lose their protection guaranteed by humanitarian law and can be the target of attack if these civilian objects are used to achieve a military advantage. Based on the elucidation of various primary sources like legislations and case laws along with secondary sources like legal textbooks and commentaries, law review articles, and legal encyclopedias, the paper generated is descriptive with a slight element of critical analysis of the international legal framework.